ISLAM DAN GLOBALISASI: KAJIAN TAFSIR MAUDHU’I - Miftahul Jannah; Mochammad Lutfi Hidayat; Muhamad Akbar Bagas Permata (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This article discusses Islam and globalization which aims to reveal the meaning of globalization in the study of maudhu'i interpretations. In the current era of globalization, all aspects can be reached without being blocked by borders and can be seen by everyone in the world. Islam as a religion embraced by billions of people also faces challenges from the effects of globalization. But Islamic globalization is different from western globalization. Islamic globalization respects the existing cultural diversity, while western globalization tends to impose western values on the culture of other nations. Therefore, the interpretation of globalization has its own urgency. This paper uses the library research method obtained from several references including supporting books and websites related to the discussion. The result is that globalization in Islam is an understanding that is rooted in a written statement which states that the message of Islam is aimed not only for one ethnicity, nation, race, layer of society but Islam is comprehensive for the universe.